Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$\sum_{i=1}^n t^{i-1}$$ I am stuck with the proof of this equality.

share|cite|improve this question
up vote 3 down vote accepted

Hint: Write out the summation $$\sum_{i=1}^n t^{i-1}=1+t+t^2+\cdots+t^{n-1}$$ Now multiply by $1-t$, and observe which terms will cancel and which will survive.

share|cite|improve this answer

Use induction on $n\in \mathbb N, n\ge1$ with $P(n):=\sum_{i=1}^n t^{i-1}=\frac{1-t^n}{1-t}$: For $n=1$ you have: $$P(1): 1=\frac{1-t}{1-t}$$ which is correct. Suppose that $P(n)$ is true, now check it for $n+1$. You have $$P(n+1): \sum_{i=1}^{n+1} t^{i-1}=\sum_{i=1}^n t^{i-1}+t^{n+1}=\frac{1-t^n}{1-t}+t^{n+1}=\frac{1-t^{n+1}}{1-t}$$ So the statement is true for any $n\in\mathbb N$.

share|cite|improve this answer

Use perturbation method from Concrete Mathematics: $$ S_n=\sum_{k=1}^{n}t^{i-1}\\ S_{n+1}=S_n + t^{n}=\sum_{k=1}^{n}t^{k} + 1=t\sum_{k=1}^{n}t^{k-1}+1=t S_n + 1 $$ After the algebra you get $$ S_n=\frac{1-t^{n}}{1-t} $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.